Trade and industrial development in Africa : rethinking strategy and policy - Moyo, Theresa (UPCC book collections on Project MUSE. Political Science and Policy Studies., 2014)
This book revisits the perennial challenge that scholars, economists, and politicians have been grappling with since the 1960s. Development, in this book, has been defined in a context that projects it as a multidimensional and complex process which seeks to enhance the human, social, economic and cultural welfare of the people. This book calls for a rethinking of trade and industry for Africa's development. It uses data drawn from national development plans and strategies, and trade and industry issues have been prioritized at the continental level, in key policy documents. On the whole Africa's industry and trade performance have been poor in spite of national, regional, and continental plans. The contributors to this volume propose some alternative strategies and policies which are necessary for trade and industry to grow and contribute to the wellbeing of Africa's people.